The words of youth against corruption - V. A. Kolesnikov (Современная наука и инновации, 2024)
This work is devoted to a rather important topic in the field of combating corruption in the Russian Federation, namely the role of youth in resolving this issue, as well as their attitude to corruption as a harmful phenomenon in general. Corruption covers all segments of the population and exists in almost all world states of the present time, causing incalculable damage to both individuals and organizations, and the entire state in general. The relevance of the topic under study is determined by its ubiquity and the need to solve the problem in the modern world. The need to eliminate corruption is determined by the magnitude of the consequences inflicted on the whole society by this harmful phenomenon. In particular, it is possible and necessary to talk about the relationship of consciousness and worldview of the younger generation with the degree of prevalence and increase in the number of cases of corruption in all spheres of public life. The purpose of this research work is to study corruption phenomena among young people, identify the main causes and ways to minimize corruption. Accordingly, corruption in all its most diverse forms is put forward as the subject of research, paying important attention to its direct relationship with the younger generation. In the course of the work, such theoretical and empirical methods as comparison, analysis, classification, testing, questioning, observation, study, calculations and others were used and applied. The scope of application of the results obtained during the writing of a scientific article and conducting social surveys covers a wide range of public and government activities. The work carried out and its results may influence further decisions in the field of anti-corruption policy at both the federal, regional and municipal levels, as well as the results of this scientific work should have an appropriate impact on readers' views on corruption and corruption policy in the Russian Federation and show the degree of importance and role of youth not only in its appearance and existence, but also in overcoming it or, at least, minimizing it. And, of course, this article will provide a fresh look at the problem under study directly on behalf of a representative of the younger generation, which is the author of the work. Based on the results of the work, the need to resolve the problem of corruption was justified, the causes of its occurrence, ways of elimination, types of these very corruption phenomena relative to the strata of the population and the level of power in which it can manifest itself were comprehensively studied and given in the text of the article, the involvement of the younger generation in its appearance and elimination was revealed and finally, the relevant conclusions regarding the studied topic are presented.